Analisis Kendala Pembelajaran IPS terhadap Isu Global Yang Dipengaruhi Kemajuan Teknologi - Dzikra Tsabita Azalea; Aisyatun Munawaroh; Didik Tri Setiyoko (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to analyze the obstacles in Social Studies (IPS) learning related to global issues influenced by technological advancement through a literature review method. Social Studies plays an essential role in shaping students’ understanding of social, economic, cultural, and political life while fostering global awareness in the digital era. However, in practice, IPS learning often faces various challenges that reduce its effectiveness and attractiveness. One of the main problems is students ’low interestin IPS, as it is often perceived as boring and overly theoretical, combined with the influence of technology that diverts students’ attention toward digital entertainment. Other contributing factors include non-interactive teaching methods, limited learning facilities, unconducive classroom environments, and a lack of parental support. Through a comprehensive literature review, this study found that relevant strategies to overcome these issues include Project-Based Learning, Technology Integration, and Contextual Approaches. These strategies enable students to learn actively, critically, and collaboratively by linking IPS material to global issues and real-world phenomena. The recommended solutions include implementing project-based education, utilizing interactive digital media, and fostering intercultural dialogue within the learning process. The results of this study are expected to provide theoretical contributions to the development of adaptive IPS learning models in response to technological progress, as well as practical benefits for teachers, schools, and policymakers in creating Social Studies learning that is engaging, meaningful, and relevant to the global challenges of the 21st century.